The silencing of unifying tribes: the colonial construction of tribe and its 'extraordinary leap' to nascent nation-state formation in Western Sahara - Isidoros, K (Anthropological Society of Oxford, 2015)
Scholarship has glossed over an ‘extraordinary leap' of Sahrāwī tribes to citizens of an exiled nation state in response to the threat to territorial sovereignty from failed decolonisation and invasion. The emergence of Sahrāwī nationalism has become entangled in problematic discourses of tribalism and been posited as an a priori result of detribalisation. This article examines the Spanish colonial construction of the enigma of tribe, showing how it has become misread and ossified in post-colonial overlays of scholarship. The Sahrāwī political vocabulary that has been obscured in the colonial records offers a more nuanced analysis of the silencing of unifying tribes and charts the move from a customary form of centralised political organisation to the contemporary nation state.